Evidence of Pituitary Hypoplasia Associated with Partial Central Diabetes Insipidus in a Young Persian Cat - Degregori, Emanuelle Bortolotto; Pippi, Matheus Da Rosa; De Moura, Ana Lúcia Ottolia Niederauer; Soila, Rogério; Furtado, Priscila Viau; Pöppl, Álan Gomes (Acta Scientiae Veterinariae, 2020)
Background: Congenital anomalies are an uncommon pituitary hypofunction cause associated to multiple hormone deficiencies. Congenital hyposomatotropism is often related to an inherited anomaly, characterized mainly by delayed growth. It is not uncommon to find associated thyroid-stimulating hormone and gonadotropin deficiencies. Pituitary malformation may be associated to progressive cystic lesion expansion. Central diabetes insipidus (CDI) is another rare disease associated to polyuria (PU) and polydipsia (PD) secondary to antidiuretic hormone (ADH) deficient secretion. The aim of this report is to describe a likely case of pituitary hypoplasia, associated with partial CDI in a cat. Case: A 9-month-old unneutered male Persian cat weighing 2 kg was presented due to severe polyuria and polydipsia associated with growth deficit when compared with its sibling. After clinical and laboratory evaluations during the months in which the patient was monitored, a reduced serum concentration of insulin-like growth factor-1 (IGF-1), thyroid-stimulating hormone (TSH), thyroid hormones, and testosterone was documented, confirming the diagnosis of hyposomatotropism, hypogonadism, and secondary hypothyroidism. Furthermore, therapeutic diagnosis with desmopressin revealed partial central diabetes insipidus (CDI). As the sibling showed normal development aging 13-months, a radiographic examination of the forelimb (carpus) was performed on both cats. There was lack of growth plate fusion in the patient, without any other evidence of dysgenesis, whereas complete epiphyseal closure was observed in the sibling. Despite desmopressin and levothyroxine therapeutic prescription the owners refuse further follow-up to the case. Discussion: Notwhistanding neuroimaging was not available for investigation of pituitary aspect in this particular case, the clinical symptoms added to the results of the complementary tests were consistent with pituitary hypoplasia, associated with hyposomatotropism, secondary hypothyroidism, hypogonadism, and partial CDI. Hyposomatotropism was presumably diagnosed based on the patient’s clinical characteristics, which included proportional growth delay, delayed tooth eruption, delayed growth plate fusion, associated with serum reduced IGF-1 results in comparison with its sibling. The report of low free T4 by equilibrium dialysis and of low total T4 levels, associated with low TSH levels, was considered compatible with secondary hypothyroidism. TRH stimulation test is considered the gold standard for secondary hypothyroidism diagnosis since low TSH could be secondary to assay´s low sensibility. However, normal TSH and thyroid hormone results in the sibling results ruled out this possible dismissed diagnose. The patient’s lack of sexual interest, associated with hypotestosteronemia and underdeveloped genitals (absence of penile spines and testicular hypoplasia), indicates hypogonadism. Finally, partial CDI diagnosis was demonstrated by cat´s partial ability to increase urinary specific gravity under water deprivation often made by the owners, as well as the response pattern to desmopressin therapy. Owing the lack of neurological signs expected to be associated with neoplastic or traumatic hypopituitarism etiology, hypoplasia hypothesis was raised. Quite often, patients with pituitary hypoplasia develop Rathke cleft cysts that might expand over time. In the present case, partial CDI is likely to be caused by the compression of the neurohypophysis by cyst formation secondary to adenohypophyseal hypoplasia since this kind of pituitary congenital anomaly does not justify per se neurohypophysis implications.